Poverty and everyday urban space in Niamey - (:unkn) unknown (My University, 2000)
In fast-growing sub-Saharian African cities, unplanned settlements and suburban villages usually accommodate the most disadvantaged urban dwellers, who are also the least mobile. Data from a household survey carried out in Niamey on a sample of 2,732 people make it possible to analyse their housing and social characteristics and the way they use urban space. Personal income is a more decisive factor in access to the city than home location, but for the urban poor, lack-of-income effects are compounded by home location in peripheral areas, which are usually both under- serviced and difficult to access. This cumulation of handicaps strongly reduces the possibility of travelling "to town" and therefore, of access to better paid jobs and, more generally, to urban services.
Keywords: African Research